A Genomic Profile of the Immune Response to Stroke With Implications for Stroke Recovery. (May 2015) - Barr, Taura L.; VanGilder, Reyna; Rellick, Stephanie; Brooks, Steven D.; Doll, Danielle N.; Lucke-Wold, Ann Noelle; Chen, Dongquan; Denvir, James; Warach, Steven; Singleton, Andrew; Matarin, Mar
Objectives: The objectives of this study were to determine the change in gene expression between two time points following stroke and to identify biomarkers of stroke recovery through gene expression profiling and pathway analysis. Methods: Peripheral blood was collected from 34 ischemic stroke patients (confirmed by magnetic resonance imaging) ≥18 years of age, within 24 hr of symptom onset and 24–48 hr later, and from healthy controls. The Modified Rankin Scale (MRS) was used to determine 30-day recovery. Total RNA was extracted from whole blood in Paxgene RNA tubes, amplified, and hybridized to Illumina HumanRef-8v2 bead chips. Gene expression was compared in a univariate manner between stroke patients at both time points and good versus bad outcome using t -test in GeneSpring. Inflation of Type 1 error was corrected by false discovery rate (FDR), and Ingenuity Systems Pathway analysis (IPA) was performed. A secondary validation cohort was recruited from a local hospital. Results: Three genes were significantly downregulated over time ( LY96, IL8, and SDPR ; FDR corrected p < .05). This finding was confirmed in a validation cohort of stroke patients ( n = 8). IPA revealed cytotoxic T-lymphocyte antigen 4 (CTLA4) signaling was the most significant pathway present in the peripheral whole blood of stroke patients 24–48 hr after onset. When controlling for age and National Institutes of Health Stroke Scale score, high baseline expression of TLR2 and TLR4 significantly predicted worse scores on the MRS. Conclusion: CTLA4 signaling is a novel pathway for the study of stroke-induced immune suppression. Markers of immune dysfunction early after stroke may prove useful for identifying patients with increased risk of poor recovery.